Respostas
respondido por:
4
(x - 0)² + (y - (-2))² = 4²
x² + (y + 2)² = 16 (essa é a equação reduzida dessa circunferência)
Desenvolvendo, temos a equação geral:
x² + y² + 4y + 4 - 16 = 0
x² + y² + 4y - 12 = 0 (essa é a equação geral dessa circunferência)
x² + (y + 2)² = 16 (essa é a equação reduzida dessa circunferência)
Desenvolvendo, temos a equação geral:
x² + y² + 4y + 4 - 16 = 0
x² + y² + 4y - 12 = 0 (essa é a equação geral dessa circunferência)
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás